2022
DOI: 10.1088/1741-4326/ac7ed7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-field and parallel dynamics of SOL filaments in TCV

Abstract: Using recently installed scrape-off layer diagnostics on the tokamak à configuration variable, we characterise the poloidal and parallel properties of turbulent filaments. We access both attached and detached divertor conditions across a wide range of core densities (f G ∈ [0.09, 0.66]) in diverted L-mode plasma configurations. With a gas puff imaging (GPI) diagnostic at the outer midplane we observed filaments with a monotonic increase in radial velocity (from 390 m s−1 to 800 m s−1) and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
6
16
0
Order By: Relevance
“…In particular, in this analysis the blobs are seen to become bigger in size as α t increases, mainly related to a corresponding increase of their radial propagation velocity by means of equation (11), while neither the FWHM of the filament waveforms nor the poloidal velocity show any clear trend. This observation is well in line with previous H-mode studies on ASDEX-Upgrade [14,19] as well as a recent L-mode analysis on TCV [55] showing that a higher resistive-interchange turbulence activity close to the separatrix, resulting from an increase in gas fuelling and therefore separatrix collisionality, drives bigger and radially faster filaments to be expelled into the far SOL. Finally, in figure 10 it is also shown by means of the color map that the blob properties are substantially independent of their radial position across the SOL.…”
Section: Filament Parameterssupporting
confidence: 91%
“…In particular, in this analysis the blobs are seen to become bigger in size as α t increases, mainly related to a corresponding increase of their radial propagation velocity by means of equation (11), while neither the FWHM of the filament waveforms nor the poloidal velocity show any clear trend. This observation is well in line with previous H-mode studies on ASDEX-Upgrade [14,19] as well as a recent L-mode analysis on TCV [55] showing that a higher resistive-interchange turbulence activity close to the separatrix, resulting from an increase in gas fuelling and therefore separatrix collisionality, drives bigger and radially faster filaments to be expelled into the far SOL. Finally, in figure 10 it is also shown by means of the color map that the blob properties are substantially independent of their radial position across the SOL.…”
Section: Filament Parameterssupporting
confidence: 91%
“…The additional problem that we are addressing, facilitating closer experimental comparisons with theoretical models of blob transport, is essential for experimental validation tests of these models. These tests of the models (e.g., 14 ) are made more valuable with accurate determinations of the size, shape, and motion of blobs.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional approaches to blob analysis include a family of conditional averaging methods, custom-made workflows that track high signal regions, and spatio-temporal cross-correlation techniques 5 , 14 , 15 . The conditional averaging methods and the cross-correlation techniques have the limitations of only providing averaged characteristics of blobs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004; Myra, Russell & D'Ippolito 2006 b ; Russell, Myra & D'Ippolito 2007; Offeddu et al. 2022) have been active research topics. Earlier simulation work demonstrated that the sheared E × B flow plays a crucial role in the turbulence transport (Burrell 1998) and can also stop the blob radial motion within the shear layer (Ghendrih et al.…”
Section: Introductionmentioning
confidence: 99%